The euro area's Achilles heel: Reassessing Italy's long decline in the context of European integration and globalisation - Dario Guarascio; Philipp Heimberger; Francesco Zezza (The Vienna Institute for International Economic Studies (wiiw), 2023)
This paper analyses how Italy's decades-long decline turned the country into the euro area's Achilles heel, the most vulnerable spot in the common currency. We use a structuralist framework to synthesise different (competing) supply-side and demand-side explanations, accounting for long-term processes and sectoral interdependencies. We argue that structural domestic factors that were already present in the decades after World War II ('original sins') - low-cost competition and labour fragmentation, many small firms linked to low innovation, and a deep territorial divide - interacted with the policy constraints brought about by globalisation and European integration to exacerbate Italy's decline vis-à-vis its euro area peers.
Keywords: E65; P16; F45; F62; 330; Italy; decline; euro area; crisis